Personal And Professional Characteristics Of A Good Muslim Doctor: Perception Of Newly Graduated Doctors - AN, Azmi; J, Jamilah; MR, Dzulkhairi; S, Ramli; O, Ariff; NM, Nasri Ismail (IIUM Medical Journal Malaysia, 2016)
Introduction: The Medical Faculty of Universiti Sains Islam Malaysia (USIM) aims to produce good Muslim doctors (GMD) who are able to practise medicine that is integrated with Islamic values. Islamic courses and Medical Ethics are integrated into the curriculum in its effort to provide adequate Islamic knowledge and nurturing professionalism as a process of personal and professional development (PPD) within the framework of Islamic teaching. The objective of the study was to evaluate the perception of graduates and students of characteristics of a GMD. Method: A self-administered questionnaire was distributed to the participants. The respondents were asked to rate their level of agreement or disagreement on the statements that represent the characteristics of a GMD. Statistical analysis of the data was carried out using SPSS version 18.0. The mean, median and inter quartile ranges of the characteristics were determined and differences between the groups were analysed using Mann-Whitney U test. Results: Results showed significant difference between gender for the item “Conscious of professional ethics” (p=0.021). Significant differences were seen in the median scores between the graduates and the final year students in four out of six items for personal characteristic. Conclusion: Islamic input in the medical curriculum and the teaching of professionalism has an impact on graduate perception of characteristics of a GMD. Further improvement in the teaching of professionalism among undergraduates is necessary in order to promote greater impact on the understanding and internalization of characteristics of a GMD. The Islamic input in the medical curriculum can thus be regarded as the blueprint for PPD of medical undergraduates to become a GMD.